Introduction: Critical Perspectives on Contemporary Spanish Poetry - Andrew P. Debicki (Studies in 20th & 21st Century Literature, 1992)
Introduction to the special issue
Keywords: contemporary Spanish poetry; Spanish poetry; poetry; introduction; history of Spanish poetry; Spanish Civil War; Francisco Franco; historical perspective